Sludge carbonization and activation: From hazardous waste to functional materials for water treatment. Issue 4 (December 2016) - Cheng, Fangwei; Luo, Hongxi; Hu, Lei; Yu, Bin; Luo, Zhen; Fidalgo de Cortalezzi, Maria
Abstract: The utilization of sludge from wastewater treatment plants as adsorbent material was investigated. Dry sludge from Ezhou Qingyuan sewage treatment plant (Hubei, China) was heated in anaerobic conditions to produce carbonized sludge, that further chemically activated at higher temperatures and K2 CO3 to enhance porosity and surface area. The materials were characterized by scanning electron microscopy (SEM), Fourier transformed infrared spectroscopy (FTIR). thermo gravimetric analysis (TGA) and nitrogen adsorption isotherms. TGA curves showed water and low molecular weight organics were lost in a first stage, with the onset of decomposition at 300 °C and up to 700 °C; activation resulted in further carbonization. Nitrogen adsorption experiments yielded Type IV isotherms, characteristic of mesoporous materials. Activation greatly increased surface area, reaching up to 642 m 2 /g. FTIR spectra showed the formation of a carboxyl-metal complex at activation, but no further changes in functional groups with increasing reaction temperature. The adsorption capacities of carbonized and activated sludge towards Rhodamine B were investigated by batch and kinetic experiments. Adsorption increased with activation temperature, reaching a maximum at 700 °C with the exception of the sample carbonized at 500 °C where a monotonic increase in capacity was observed. Isotherms showed Langmuir-type behavior; kinetic data was successfully fitted to a pseudo second order model. The adsorption was not affected by pH changes or dissolved solids type and concentration. Zeta potential determinations showed minimal variation of surface charge in the pH range of interest. The results indicated that sludge carbonization is a promising sustainable technology for mass sludge treatment.